Archives en bibliothèques (XVIe-XXIe siècles) - Chapron, Emmanuelle; Henryot, Fabienne (Métamorphoses du livre, 2023)
Are libraries archival repositories and if so, what do they archive and how do they do it? This book proposes to discuss the relevance of the generally accepted boundaries between archives and libraries and to examine the long-term construction of document curation and the functions, at times quite distinct, at times more hybrid, that European societies attributes to them. Using case studies, the sixteen contributions in this volume trace the circumstances in which certain types of documents were considered as archival materials and how they were distributed in archives or libraries. They examine the criteria that served as a basis for such an institutional and documental distinction, and the way in which these choices conditioned sorting, selection, classification and consultation endeavours. They thus invite us to re-examine the genesis of documental collections, within families, State institutions or scholars' studies, and to shed new light on the conditions of the making of history, then and now.